Progression-free survival at 24 months as a predictor of survival outcomes after CHOP treatment in patients with peripheral T-cell lymphoma: a single-center validation study in a Japanese population. Issue 8 (3rd July 2021) - Shirouchi, Yuko; Yokoyama, Masahiro; Fukuta, Takanori; Uryu, Hideki; Nishimura, Noriko; Mishima, Yuko; Inoue, Norihito; Tsuyama, Naoko; Takeuchi, Kengo; Terui, Yasuhito
Abstract: Peripheral T-cell lymphoma (PTCL) is a group of aggressive lymphomas commonly treated with cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP). Progression-free survival at 24 months (PFS24) constitutes a survival predictor for some lymphomas but has not been examined in Asian populations. We retrospectively investigated whether PFS24 was predictive of survival outcomes after CHOP treatment in 73 Japanese patients with PTCL. Patients without PFS24 had shorter median subsequent overall survival (OS) (20.2 vs. 121.0 months, p < 0.001) and shorter median subsequent progression-free survival (5.0 vs. 17.1 months, p = 0.03). Patients without PFS24 had worse overall (62.5% vs. 100%) and complete response rates (45.8% vs. 96.0%) (both p < 0.001). PFS24 absence (hazard ratio: 3.34, p = 0.004) and poor performance status (hazard ratio: 3.17, p = 0.04) were independently predictive of shorter OS. These findings suggest that PFS24 is predictive of survival after CHOP treatment in Japanese patients with PTCL.